+0  
 
0
645
1
avatar

log72 (x2 - x) = 1

Guest Jan 30, 2015

Best Answer 

 #1
avatar+87293 
+5

log72 (x2 - x) = 1

In exponential form, we have

72^1 = x^2 - x  rearrange

x^2 - x - 72 = 0     factor

(x - 9) (x + 8) = 0   and setting each factor to 0, we have that x = 9 and x = -8

And both solutions "work".....

 

CPhill  Jan 30, 2015
 #1
avatar+87293 
+5
Best Answer

log72 (x2 - x) = 1

In exponential form, we have

72^1 = x^2 - x  rearrange

x^2 - x - 72 = 0     factor

(x - 9) (x + 8) = 0   and setting each factor to 0, we have that x = 9 and x = -8

And both solutions "work".....

 

CPhill  Jan 30, 2015

6 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.